2020
DOI: 10.3389/fgene.2019.01375
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Implication of Long Non-Coding RNAs SOX2 Overlapping Transcript and Its Potential Target Gene Network in Various Cancers

Abstract: Background: SOX2 overlapping transcript (SOX2-OT) produces alternatively spliced long non-coding RNAs (lncRNA). Previous studies of the prognostic role of SOX2-OT expression met with conflicting results. The aim of this study was to properly consider the prognostic role of SOX2-OT expression in several cancers. In addition, the regulative mechanism of SOX2-OT is explored. Methods: PubMed, EMBASE, and Cochrane Library and The Cancer Genome Atlas (TCGA) database were comprehensively explored to recover pertinent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Similar results have reported a prognostic role for SOX2-OT in malignant diseases, with a meta-analysis which indicates that increased SOX2-OT expression is significantly associated with poor overall survival (OS), and short disease-free survival (DFS) in osteosarcoma and gastric cancer patients [32]. In the case of lung cancer, some studies have previously reported that SOX2-OT overexpression is associated with worse clinical…”
Section: Similar Findings Have Been Reported In Laryngeal Squamous Cesupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results have reported a prognostic role for SOX2-OT in malignant diseases, with a meta-analysis which indicates that increased SOX2-OT expression is significantly associated with poor overall survival (OS), and short disease-free survival (DFS) in osteosarcoma and gastric cancer patients [32]. In the case of lung cancer, some studies have previously reported that SOX2-OT overexpression is associated with worse clinical…”
Section: Similar Findings Have Been Reported In Laryngeal Squamous Cesupporting
confidence: 67%
“…outcomes, suggesting a role as an independent prognostic factor, though the data remains inconclusive thus far [22,32]. The MTA3/SOX2-OT/SOX2 axis has been involved as a prognostic factor for poor clinical outcomes in esophageal squamous cell carcinoma patients [40].…”
Section: Similar Findings Have Been Reported In Laryngeal Squamous Cementioning
confidence: 99%
“…The regulatory role played by SOX2‐OT in human diseases including bipolar disorder and schizophrenia is important 25,26 . Furthermore, SOX2‐OT can predict poor overall and disease‐free survival, and correlates with tumor development and metastasis; thus, it serves as a novel diagnostic marker and plays oncogenic roles in many cancers 27,28 . The expression of SOX2‐OT gradually increases in healthy persons, and in patients with end‐, and non‐end‐stage HF 29 .…”
Section: Discussionmentioning
confidence: 99%
“…SOX2-OT has been identified as a novel lncRNA that can serve as a prognostic biomarker for cancers. A high level of SOX2-OT correlates well with poor clinical outcomes in cancers [ 34 45 ]. Li et al performed a meta-analysis of 13 selected studies by a comprehensive search of PubMed, EMBASE, Cochrane Library, and TCGA and found that the elevated SOX2-OT expression is significantly related to shorter overall and disease-free survival times in cancer patients [ 45 ].…”
Section: Sox2-ot Is An Oncogene and A Biomarker For Cancersmentioning
confidence: 99%
“…A high level of SOX2-OT correlates well with poor clinical outcomes in cancers [ 34 45 ]. Li et al performed a meta-analysis of 13 selected studies by a comprehensive search of PubMed, EMBASE, Cochrane Library, and TCGA and found that the elevated SOX2-OT expression is significantly related to shorter overall and disease-free survival times in cancer patients [ 45 ]. Cancer patients with high SOX2-OT expression are more likely to have an advanced clinical stage, earlier lymphatic metastasis, earlier distant metastasis, a larger tumor size, and more extreme tumor invasion than those with low SOX2-OT expression [ 45 ].…”
Section: Sox2-ot Is An Oncogene and A Biomarker For Cancersmentioning
confidence: 99%